Flow boiling pressure drop of R-1270 in 1.0 mm tube - Diehl de Oliveira, Jeferson (2023)
This study experimentally investigated the flow boiling pressure drop and flow patterns of R-1270 in a horizontal circular tube with 1.0 mm ID. The experiments were carried out with mass flux between 240 and 480 kg/(m2s) and heat flux ranging from 5 to 60 kW/m2 at a saturation temperature of 25 °C. Flow patterns and void fraction distribution among channels were observed with a high-speed camera in a visualization section. The influence of mass flux and vapour quality on pressure drop was verified. The flow patterns identified during tests were plug, slug churn and wavy-annular, differently distributed along the channels. The results were also compared with eight different correlations proposed in the literature. Results indicate the dependence of pressure drop on both mass and vapour quality.